Regulating Foreign Economic Activity of Enterprises of Non-Ferrous Metallurgy in Russia in Conditions of Global Crisis - Ya. A. Kalitskiy (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Non-ferrous metallurgy, as one of principle industries of Russian economy, since the beginning of the global geopolitical crisis has been facing a number of serious problems, including distribution restrictions. In such circumstances iron and steel companies need state support. To develop foreign economic activity business requires not only fast re-orientation to new markets but also thorough help. In case of situation deterioration direct regulation of foreign economic activity of producers will become important. In view of this setting-up of a specialized agency, which could supervise foreign economic activity of the most important industries and support key enterprises can be useful. Its functions can include talks and contract operations and compensations for companies with short-received profits under their contracts. In such cases key factors affecting the amount of compensation shall be taken into account. The author proposed a formula, which can help estimations made by the agency.